Objectifying Discourse and Subjectivity in Martin Heidegger’s Frühe Freiburger Vorlesungen (1919-1923) - Bertorello, Adrián (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
This study focuses on Frühe Freiburger Vorlesungen (1919-1923), and offers an interpretation of the subjectivity theory implied in objectifying discourses (science and philosophy). The interpretation of this period in Heidegger’s thought is the following: Objectifying discourses appear as a modal transformation of subjectivity that can be explained in semantic terms through the idea of desembrague (disengaging). In fact, the constitution of a world as an event (Vorgang), or equivalently, as a relation in which the self is placed as the subject of knowledge before objects, can only be elaborated if the enunciation stage is avoided and an idea denying the three deictics («self», «here» and «now») is created. Heidegger calls this process of desembrague ¡ (disengaging) as Ent-lebung.
Keywords: theory; modality; science; subjectivity; disengaging